Istikhdam Wasīlat al-Kurrah al-Dawwārah li-Taḥsīn Itqān al-Mufradāt al-‘Arabiyyah li-Ṭālibāt al-Duf‘ah al-Khāmisah bi-Ma‘had Taḥfīẓ al-Qur’ān Dār al-Furqān bi-Fālūfū - Putra, Alfan; Mawardi; Izzatul Khalifah Kadir (Institut Agama Islam Negeri (IAIN) Palopo, 2024)
The research discusses the use of the rolling ball method to improve the mastery of Arabic vocabulary among the fifth batch of students at Dar Al-Furqan Quran Memorization Institute in Palopo. The objectives of the research are: (1) to understand the application of the rolling ball method to improve the mastery of Arabic vocabulary among the fifth batch of students at Dar Al-Furqan Quran Memorization Institute in Palopo, and (2) to understand the results of applying the rolling ball method. The type of research used is action research, and the data collection methods are work observation, field observation, and a test paper. The research results are: (1) The percentage increase in the first cycle can be observed, where out of 8 students, 7 students completed the percentage (87.5%), while one student did not complete the percentage (12.5%). Meanwhile, in the second cycle, all eight students completed the percentage (100%). From the first cycle to the second cycle, there was an increase in learning outcomes by (12.5%). Thus, in the second cycle, it is said that the learning outcomes were completed. يناقش البحث في هذه الرسالة استخدام وسيلة الكرة الدوارة لتحسين إتقان المفردات العربية لطالبات الدفعة الخامسة بمعهد تحفيظ القرآن دار الفرقان بفالوفو. أهداف البحث هي: (1) معرفة تطبيق وسيلة الكرة الدوارة لتحسين إتقان المفردات العربية لطالبات الدفعة الخامسة بمعهد تحفيظ القرآن دار الفرقان بفالوفو، (2) معرفة نتائج تطبيق وسيلة الكرة الدوارة. نوع البحث المستخدم هو البحث الإجرائي، وأساليب جمع البيانات هي مراقبة العمل، والملاحظة الميدانية، وورقة الاختبار. نتائج البحث هي: (1) نسبة الزيادة في الدورة الأولى يمكن ملاحظتها، حيث من بين 8 طالبات، 7 طالبات أكملن النسبة (87.5٪)، في حين أن طالبة واحدة لم تكمل النسبة (12.5٪). وفي الوقت نفسه، في الدورة الثانية، أكملت جميع الطالبات الثمانية النسبة المئوية (100٪). ومن الدورة الأولى إلى الدورة الثانية، حدثت زيادة في نتائج التعلم بنسبة (12.5٪). وهكذا، في الدورة الثانية، يُقال إن نتائج التعلم قد اكتملت.